Dieback of cork oak (Quercus suber) in Catalonia (NE Spain) caused by Botryosphaeria stevensii - LUQUE, J; Girbal, J (European Journal of Forest Pathology, 1989)
Botryosphaeria stevensii Shoemaker (anamorph: Diplodia mutila Fr. apud Mont.) is reported as the cause of canker and dieback of cork oak (Quercus suber L.) in Catalonia (NE Spain). It also causes wilting of trees after cork is removed for industrial purposes. Symptomatology and details of morphology for both anamorph and teleomorph are given.
Keywords: Botryosphaeria stevensii; canker; Cork oak; dieback; diplodia mutila; morphology (PG); Symptoms